Phosphorus recovery as struvite: recent concerns for use of seed, alternative Mg source, nitrogen conservation and fertilizer potential - Kataki, Sampriti; West, Helen M.; Clarke, Michèle L.; Baruah, Debendra C. (Elsevier, 2016)
Finite availability of phosphorus (P) resources makes recovery of this non-substitutable plant nutrient from alternative waste sources an increasingly attractive option of renewed interest. In this context, feasibility of struvite (MgNH4PO4·6H2O) recovery, an alternative P fertilizer is already demonstrated at laboratory scale from range of waste streams of farm, municipal and industrial origin, with reasonably high orthophosphate recovery efficiency (∼90%). However, apart from a few commercial extraction units using municipal sludge and urine, large scale struvite recovery is not widely adopted for many of these sources. Moreover, need of some research interventions that are restricting its profitable recovery are also highlighted by earlier studies. To increase recovery efficiency from identified potential sources in terms of cost and energy input, research focuses on some new aspects of the process such as prospects of alternative recyclable magnesium sources, different seed materials and their related issues, which are analyzed in this review. Prospects of nitrogen conservation through struvite recovery and fertilizer value of struvite considering its properties, comparative performance with conventional fertilizer and interaction with soil and plant growth are also critically reviewed.